Diary of a wimpy kid : the getaway - Kinney, Jeff (Kinney, Jeff. Diary of a Wimpy Kid, 2017)
Greg Heffley and his family escape to a tropical island resort for some much-needed rest and relaxation, but sun poisoning, stomach troubles, and venomous creatures all threaten their vacation.